Beyond Conviction-Based Forfeiture: Legal Politics and Legislative Directions of Non-Conviction-Based Asset Forfeiture in the Recovery of Corruption Assets in Indonesia - Geza Tristanti Wardani; Satya Graha Habibilah (Istinbath : Jurnal Hukum, 2025)
The low rate of asset recovery resulting from corruption shows that Indonesia's asset forfeiture regime, which is still oriented towards conviction-based forfeiture, has not been effective in addressing the complex and transnational nature of modern corruption. In the 2021–2023 period, state financial losses due to corruption reached hundreds of trillions of rupiah, while the rate of asset recovery still showed a significant percentage, especially when the perpetrators could not be prosecuted because they had fled, died, or were outside the jurisdiction, resulting in the state losing its authority to confiscate corrupt individuals’ assets. This study analyzes the legal politics of state asset forfeiture in corruption cases and assesses the urgency of implementing non-conviction-based asset forfeiture (NCB) in Indonesia’s legal system. This study adopts a normative juridical approach with legal political analysis through a review of legislation, court decisions, and relevant literature. The results of the study show that the stagnation in the ratification of the Asset Forfeiture Bill is not solely due to technical legislative issues but reflects a legal political configuration that still places the punishment of perpetrators as the main orientation, while asset recovery is not yet a legal policy priority. Additionally, the absence of a specific asset forfeiture law has led to an excessive reliance on conventional criminal mechanisms and created a legal vacuum in certain situations. This is exacerbated by institutional capacity constraints, weak coordination among law enforcement agencies, and suboptimal cross-border asset-tracing mechanisms. This study concludes that the implementation of non-conviction-based asset forfeiture (NCB) is urgently necessary to strengthen asset recovery in Indonesia, as long as it is designed within the framework of the rule of law, which guarantees judicial oversight and the protection of human rights. [Rendahnya tingkat pemulihan aset hasil tindak pidana korupsi menunjukkan bahwa rezim perampasan aset di Indonesia yang masih berorientasi pada conviction-based forfeiture belum efektif menjawab karakter korupsi modern yang kompleks dan transnasional. Dalam periode 2021–2023, kerugian keuangan negara akibat korupsi mencapai ratusan triliun rupiah, sementara tingkat pengembalian aset masih menunjukan nilai persentase yang signifikan, terutama saat pelaku tidak dapat diadili karena melarikan diri, meninggal dunia, atau berada di luar yurisdiksi sehingga negara kehilangan otoritasnya untuk merampas aset dari tindak pidana korupsi. Penelitian ini bertujuan menganalisis politik hukum perampasan aset negara dalam perkara korupsi dan menilai urgensi penerapan Non-Conviction Based Asset Forfeiture (NCB) dalam sistem hukum Indonesia. Penelitian ini menggunakan pendekatan yuridis normatif dengan analisis politik hukum melalui kajian peraturan perundang-undangan, putusan pengadilan, serta literatur relevan. Hasil penelitian menunjukkan bahwa stagnasi pengesahan Rancangan Undang-Undang Perampasan Aset tidak semata disebabkan oleh persoalan teknis legislasi, melainkan mencerminkan konfigurasi politik hukum yang masih menempatkan pemidanaan pelaku sebagai orientasi utama, sementara pemulihan aset belum menjadi prioritas kebijakan hukum. Selain itu, ketiadaan undang-undang khusus perampasan aset menimbulkan ketergantungan berlebihan pada mekanisme pidana konvensional dan menciptakan kekosongan hukum dalam situasi tertentu, yang diperparah oleh keterbatasan kapasitas kelembagaan, lemahnya koordinasi antarlembaga penegak hukum, serta belum optimalnya mekanisme penelusuran aset lintas negara. Penelitian ini menyimpulkan bahwa penerapan Non-Conviction Based Asset Forfeiture (NCB) merupakan kebutuhan mendesak untuk memperkuat pemulihan aset di Indonesia, sepanjang dirancang dalam kerangka negara hukum yang menjamin pengawasan yudisial dan perlindungan hak asasi manusia].